Antimicrobial resistance: more than 70 years of war between humans and bacteria. (2nd September 2020) - Nadeem, Syeda Fatima; Gohar, Umar Farooq; Tahir, Syed Fahad; Mukhtar, Hamid; Pornpukdeewattana, Soisuda; Nukthamna, Pikunthong; Moula Ali, Ali Muhammed; Bavisetty, Sri Charan Bindu; Massa, Salvatore
Abstract: Development of antibiotic resistance in bacteria is one of the major issues in the present world and one of the greatest threats faced by mankind. Resistance is spread through both vertical gene transfer (parent to offspring) as well as by horizontal gene transfer like transformation, transduction and conjugation. The main mechanisms of resistance are limiting uptake of a drug, modification of a drug target, inactivation of a drug, and active efflux of a drug. The highest quantities of antibiotic concentrations are usually found in areas with strong anthropogenic pressures, for example medical source (e.g., hospitals) effluents, pharmaceutical industries, wastewater influents, soils treated with manure, animal husbandry and aquaculture (where antibiotics are generally used as in-feed preparations). Hence, the strong selective pressure applied by antimicrobial use has forced microorganisms to evolve for survival. The guts of animals and humans, wastewater treatment plants, hospital and community effluents, animal husbandry and aquaculture runoffs have been designated as "hotspots for AMR genes" because the high density of bacteria, phages, and plasmids in these settings allows significant genetic exchange and recombination. Evidence from the literature suggests that the knowledge of antibiotic resistance in the population is still scarce. Tackling antimicrobial resistance requires a wide range of strategies, for example, more research in antibiotic production, the need of educating patients and the general public, as well as developing alternatives to antibiotics (briefly discussed in the conclusions of this article).